Pengembangan Bahan Ajar Kalkulus Peubah Banyak Berbantuan Software Geogebra Bagi Mahasiswa Pendidikan Matematika - ANNAJMI ANNAJMI; RATRI ISHARYADI (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2020)
Variable calculus is a subject that requires students to have high mastery and competence. This is because the material presented requires students to think critically and creatively to solve problems. In fact the results of the previous semester's assessment analysis, the percentage of students who graduated with grades A or B was very low. The research method is research and development, with ADDIE development stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results of the needs analysis showed that students need teaching material for calculus variable which is assisted by a technology of mathematical applications, where students' opinions on the need for a mathematical application such as geogebra software in learning, there are 66.7% of students strongly agree, and there are 33.3% agree . The validation results show that the average of all aspects of the assessment of teaching materials obtained an average of 4.29 means that the teaching materials are valid. The results of the practicality questionnaire analysis of the 20 students who took the lecture obtained an overall average of 4.28, which means practical. The results of student responses to the teaching material questionnaire from the aspects of teaching materials and learning activities obtained an average percentage of total positive responses of students amounted to 81.67% meaning that teaching materials are effectively used by students in learning